Phenomenological study of the lived experiences of parent school counselors - Sarmiento, Eileen Mae B.
This phenomenological study explored the lived experiences of parent school counselors in parenting their own children and in counseling their students. The research aimed to understand the needs and concerns of parent school counselors, their distinct and shared socialization practices and values, the influences of the two roles with one another, and proposed programs that would address the concerns of the participants. Parent school counselors struggled in balancing the two roles as parents and as school counselors. They expressed a need for a support system, for flexible work arrangements, and for professional development opportunities to help them ease their challenges with home and work management. As regards socialization practices, they instilled collectivistic values in parenting their children while individualistic values were highlighted when counseling students. Verbal, cognitive, and behavioral approaches were the shared socialization practices in both personal and professional contexts while disciplinary practices were distinct to parenting, and theoretical orientations were more applied in counseling their students. Furthermore, this study highlighted the influence of their dual roles on their parenting and on their counseling practices. Their parenting experiences enhanced their empathy with other parents while their interactions with students and their counseling expertise enhanced their parenting skills. By understanding the unique lived experiences of parent school counselors, this research provided valuable insights to have a deeper appreciation and support for their personal and professional endeavors. The establishment of support groups, implementation of flexible work arrangements, and provision of accessible professional development programs were recommended.